Simulation training program for vacuum application to improve technical skills in vacuum-assisted vaginal delivery - Paolo Mannella; Mario Giordano; Maria Magdalena Montt Guevara; Andrea Giannini; Eleonora Russo; Federica Pancetti; Marta Caretto; Tommaso Simoncini (BMC, 2021)
Abstract Objective evaluation of technical skills of the operators during the obstetrical device application for operative vaginal delivery, named kiwi-cup in a simulation training program. Methods Thirty-five residents in obstetrics and gynecology of the University of Pisa, Italy were recruited and evaluated with an assessment scale on technical skills from 0 to 55 points. They performed various operative vaginal delivery simulations with kiwi-cup and were evaluated at time 0 by a tutor. After 8 weeks, simulation training was repeated and trainees were re-evaluated by the same tutor. Results after 8 weeks from the first simulation session, trainees have been shown to increase technical skills (46.27 ± 4.6 with p-value < 0.0001), the successful application rate (85.71% with p-value 0.0161).) and to reduce the time to complete the procedure (86.2 ± 29.9 s with p-value < 0.0001). Conclusion simulation training on operational vaginal delivery significantly increases technical skills, improves successful rate, and reduces the time taken to complete the procedure. Clinical trial registration Not applicable.